Identifying Clinical Criteria for an Expanded Targeted Approach to Screening for Congenital Cytomegalovirus Infection—A Retrospective Study - Maya Heled Akiva; Hannah Hyde-De Sousa; Valerie Lamarre; Isabelle Boucoiran; Soren Gantt; Christian Renaud; Fatima Kakkar (International Journal of Neonatal Screening, 2023)
Targeted screening for congenital CMV infection (cCMV), which entails CMV testing of infants who fail newborn hearing screening (NBHS), has become common practice. However, this strategy misses nearly all infected infants with normal hearing at birth who are nonetheless at high risk of subsequent hearing loss and would benefit from timely cCMV diagnosis. The objective of this study was to identify expanded criteria predictive of cCMV to increase the scope and utility of targeted newborn CMV screening. In this retrospective study, 465 newborns were tested for cCMV at a single tertiary care center with a targeted screening program between 2014 and 2018. Twenty-two infants were diagnosed with cCMV, representing 0.2% of the 12,189 births over this period and 4.7% of the infants tested. The highest prevalence of cCMV infection was among infants tested because of primary maternal CMV infection (8/42, 19%), followed by failed initial NBHS (10/88, 11.4%), maternal HIV infection (3/137, 2.2%), and clinical suspicion alone (5/232, 2.2%). The symptoms with the highest prevalence of infection among all infants tested included an enlarged liver and/or spleen (33.3%) (3/9), followed by petechiae (33.3%), microcephaly (9.4%), direct hyperbilirubinemia (7.7%), thrombocytopenia (6%), and growth impairment (4.3%). In addition to CMV screening of newborns who fail the NBHS, these data suggest that certain clinical signs of cCMV—in particular: thrombocytopenia, growth impairment, and HIV exposure in pregnancy—should be additional criteria for expanded targeted newborn CMV screening, where universal screening is not yet the standard of care.